Increasing Mathematics Learning Activities Through Numbered Heads Together (NHT) Cooperative Learning Models In Students - Rahmawati, Naning; Otaiwi, Ziadoon; Nakkhasen, Warud; Thãnh, Nhãn Phan (Interval: Indonesian Journal of Mathematical Education, 2023)
The purpose of this study is to see an increase in mathematics learning activity through the cooperative learning model of the numbered heads together type in class VIID students of SMP Negeri 14 Surakarta. This study uses a type of classroom action research. The subjects in this study were teachers and students of class VIID at SMP Negeri 14 Surakarta. This study consisted of 3 cycles, namely cycle 1, cycle II, and cycle III. Sources of data in this study were obtained from observation sheets of students' learning activities in cycle I, cycle II, and cycle III, observation sheets of the learning process recorded by observers, teacher and student information, places and events where the learning process took place. This research is expected to contribute to schools or in the field of education. The results of this study are that there is an increase in students' mathematics learning activities through the application of the Numbered Heads Together (NHT) cooperative learning model in learning mathematics.